2013
DOI: 10.1111/pme.12234
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Demographic Correlates of Employment vs Disability Status in a National Community Sample of Adults with Chronic Pain: Toward a Psychology of Pain Presenteeism

Abstract: Background Although chronic pain is a source of work-related disability, relatively little research has addressed the psychological factors that differentiate individuals in chronic pain who leave the workforce from those who remain on the job despite their pain. Objective The present study examined a small set of attitudinal and coping-related factors as potential correlates of pain-related disability versus continued part- or full time employment over and above the role of well-known risk factors. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…(2017) a, g Iakova et al (2012)Karoly et al (2013) d Norlund et al (2011)Strober and Arnett (2016) a Arwert et al (2017) a Dawson et al (2011) a, d De Vries et al . (2012b) Grytten et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2017) a, g Iakova et al (2012)Karoly et al (2013) d Norlund et al (2011)Strober and Arnett (2016) a Arwert et al (2017) a Dawson et al (2011) a, d De Vries et al . (2012b) Grytten et al .…”
Section: Resultsmentioning
confidence: 99%
“…(2012) f, g De Vries et al . (2012b)Karoly et al (2013) Lindell et al . (2010) b Wijnhoven et al (2007)Besen et al (2015) Cowan et al (2012) f, g Dawson et al (2011)Karels et al (2010)Mannion et al (2009) Morris and Watson (2011) d Sarda et al (2009) Spector et al (2012) Turner et al (2008)

Bold indicates studies with a low risk of bias

a Depends on the form/subscale of the factor

b Not for every moment on which the outcome is measured

c Depends on the type of disorder of the participant

d Outcomes from univariate analysis

e Depends on the gender of the participant

f Depends on the job of the participant

g Depends on the form of work participation

h  Outcomes from bivariate analysis

i Fear-avoidance beliefs for movement/physical activity

j Fear-avoidance beliefs for work

k Total fear-avoidance

…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients pursuing benefits whether through the government or private insurance such as in worker's compensation insurance may have an unconscious incentive to remain sick or at least sicker in order to obtain benefits. Karoly et al (2013) found that subjects (N = 1252) who remained at work had significantly higher adaptive coping style (non-catastrophizing, task persistence, and trust in medical care) controlling for pain severity and psychiatric illness. For patients who are undergoing stressful worker's compensation experiences, this stress has proven to negatively impact medical outcome in the short and long term (6 years) (Grant et al 2014).…”
Section: Post Morbid Functioningmentioning
confidence: 96%
“…Recent studies have identified a set of attitudinal, personality, and coping factors that distinguish between people in pain who are able to remain partially or fully employed and those who do not (de Vries et al, 2013;Karoly et al, 2013). Nevertheless, research is needed that delves more deeply into the time-and event-sensitive daily motivational patterns of working individuals with chronic pain.…”
Section: Introductionmentioning
confidence: 94%